การศึกษาเปรียบเทียบเครือข่ายชุมชนในการป้องกันไฟป่า บ้านหัวทุ่งและบ้านปางแดงใน ตำบลเชียงดาว อำเภอ เชียงดาว จังหวัดเชียงใหม่ - นินนาท ดาวรัตนหงษ์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
The research study on “A Comparative Study of Community Networks for Forest Fire Prevention of Baan Hua Tung and Baan Pang Dang Nai, Chiang Dao Sub-district, Chiang Dao District, Chiang Mai Province” aimed to 1) compare the strength of community networks of Baan Hua Tung and Baan Pang Dang Nai, Chiang Dao Sub-district, Chiang Dao District, Chiang Mai Province, 2) compare the activities used to prevent forest fire of Baan Hua Tung and Baan Pang Dang Nai, Chiang Dao Sub-district, Chiang Dao District, Chiang Mai Province, and 3) study and analyze the support from the government sector that helped in forest fire prevention project of Baan Hua Tung and Baan Pang Dang Nai, Chiang Dao Sub-district, Chiang Dao District, Chiang Mai Province. The study was a qualitative research. The primary subjects were 35 people; 17 from Baan Hua Tung and 18 from Baan Pang Dang Nai. The instruments that used to collect data were semistructured interview, using non-participant observation, studying documents and related research and then making conclusion and discussion based on the objectives. Data were analyzed using descriptive statistics and were presented to relate to the objectives. ช The results indicated that: 1. The similarity of the strength and the sustainability of community networks of Baan Hua Tung and Baan Pang Dang Nai were having the village structure, the management of forest fire prevention and having the head of the village that had a role to develop the community. The difference of the two villages was that Baan Hua Tung villagers have had conscious in forest preservation. Bann Pang Dang Nai had extension project of Pang Dang Nai royal project to suggest villagers in forming group. Bann Hua Tung had connection from five villages that used the same water source. In the contrast, Baan Pang Dang Nai tried to establish the network for forest fire prevention. The village invited the neighborhoods to join the activities. 2. The activities used to preserve natural resources of Baan Hua Tung and Baan Pang Dang Nai were similar in term of the awareness of the villagers’ forest preservation because they need to consume water and get benefit from forest. The two villages had their own tradition and activities. These are one way of forest preservation. Moreover, the youth from the two villagers had the willing to help develop their own village. The difference of the two villages was Baan Pang Dang Nai had extension-project of Pang Dang Nai royal project to suggest and support the youth. Baan Hua Tung had senior and the elders to give suggestion. 3. The government sector supported them by giving budget, knowledge, equipment and chance to go on field trip. The difference of the two villages was Baan Pang Dang Nai had the main support from the extension-project of Pang Dang Nai royal project. The royal project did not only give knowledge and budget to the village but also help develop the villagers’ career including with the development of economy, society, and environment. The villagers could extend the knowledge to develop themselves and for self-sufficiency. The suggestion from the research is that the heads of the village should create awareness on natural preservation and be a good role model. They should also create the youth create awareness on natural preservation. In addition, the government and private sectors should focus more on giving the villages knowledge than giving budget, in order that the villagers can bring the knowledge to develop their village. Moreover the government and private sectors should support the youth so that they will have awareness and can apply the knowledge to use to develop their villages and resources. It will lead to sustainable future.